1998
DOI: 10.54991/jop.1998.1275
|View full text |Cite
|
Sign up to set email alerts
|

On some plant remains from Deccan Intertrappean localities of Seoni and Mandla districts of Madhya Pradesh, India

Abstract: The paper describes dicot and monocot leaves along with some wood remains from new Deccan Intertrappean fossiliferous localities situated in the Seoni and Mandla districts of Madhya Pradesh. The leaf remains belong to Dicotyloplryllum Saporta, Phoenicites Brongniart, Amesoneuron Goeppert and the woods are represented by Hydnocarpoxylon Bande & Khatri, Polyalthioxylon Bande and Palmoxylon Schenk. Occurrence of mucilage canal in a fossil wood of palm has been reported for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…So far six fossil palm leaves have been described under this genus. They are Amesoneuron borassoides Bonde (1986) and A. deccanensis Guleria & Mehrotra, (1998) from Deccan Intertrappean beds of Madhya Pradesh and Tura Formation (Upper Palaeocene) of Garo Hills, Meghalaya, A. lakhanpalii Mehrotra (2000) from Tura Formation, Garo Hills, Meghalaya, A. manipurensis Guleria et al (2005) from the Late Eocene of Imphal, Manipur, A. sahnii Guleria et al (2000) from Lower Miocene of Kasauli Formation, Himachal Pradesh and A siwalica Prasad (2006) from Siwalik sediments of Ranital, Himachal Pradesh. A comparative study of present fossils with those above mentioned palm fossil leaves has been carried out and concluded that none of them show similarity with the present Siwalik fossils.…”
Section: Fossilmentioning
confidence: 99%
“…So far six fossil palm leaves have been described under this genus. They are Amesoneuron borassoides Bonde (1986) and A. deccanensis Guleria & Mehrotra, (1998) from Deccan Intertrappean beds of Madhya Pradesh and Tura Formation (Upper Palaeocene) of Garo Hills, Meghalaya, A. lakhanpalii Mehrotra (2000) from Tura Formation, Garo Hills, Meghalaya, A. manipurensis Guleria et al (2005) from the Late Eocene of Imphal, Manipur, A. sahnii Guleria et al (2000) from Lower Miocene of Kasauli Formation, Himachal Pradesh and A siwalica Prasad (2006) from Siwalik sediments of Ranital, Himachal Pradesh. A comparative study of present fossils with those above mentioned palm fossil leaves has been carried out and concluded that none of them show similarity with the present Siwalik fossils.…”
Section: Fossilmentioning
confidence: 99%
“…The presence of moisture loving evergreen elements signifies that the climate was tropical with plenty of rainfall. Presence of palm remains (Sahni, 1943;Guleria & Mehrotra, 1999) and Sonneratia (Srivastava, 2008) indicate swampy and near-shore conditions during the Maastrichtian-Danian in central India.…”
Section: Family-sapindaceaementioning
confidence: 99%
“…Sahni (1943) reported a palm wood, namely, Palmoxylon sclerodermum from Seoni but the exact locality was unknown. Later on, Guleria and Mehrotra 1999) reported a palm leaf Phoenicites lakhanpalii and few palm woods, viz. Palmoxylon binoriensis, P. canalosum, P. lunarianum and P. vaginatum.…”
Section: Introductionmentioning
confidence: 99%
“…Remarks-The pinnate eucamptodromous venation of the fossil at once indicates that it is a dicotyledonous leaf. The markedly curved entire margin with five pairs of alternate to sub-opposite secondaries differentiate the present specimen from the known fossil dicot leaves (Guleria et al, 1999;Mehrotra & Mandaokar, 2000). Hence, it is assigned a new species, Dicotylophyllum evansii sp.…”
Section: Holotype-specimenmentioning
confidence: 61%